(untitled) (Research, Society and Development, 2022)
Population aging deserves attention due to the biopsychosocial changes that occur with the elderly. Among these changes, the nutritional status stands out since its disturbances predispose the elderly to the onset of diseases. The present study aims to evaluate the nutritional status associated with the physical-functional situation of elderly women who practice physical activity (PAF) and those who do not practice physical activity (NPAF). This is a transversal study, with a quantitative approach, carried out with elderly women from the Universidade Aberta no Tempo Livre program of the Universidade Estadual da Paraíba and elderly women from socialization groups. The variables studied were: body mass index (BMI), handgrip strength, weight gain and loss, basic activities of daily living, number of falls, waist circumference (WC) and calf circumference (CC). In the statistical analysis a Gamma regression model was fitted. A significance level of 5% was adopted. We evaluated 35 elderly women PAF and 36 elderly women NPAF. The factor associated with BMI in the FAP elderly women was WC. Among the elderly NPAF women, BMI was associated with WC and WC. Through the knowledge of the variables that influence the BMI of the elderly PAF and NAPF, it is possible to create health strategies according to the needs of each group.